2017
DOI: 10.1152/japplphysiol.00969.2016
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of rostral fluid shift to intrathoracic airway narrowing in asthma

Abstract: In asthma, supine posture and sleep increase intrathoracic airway narrowing. When humans are supine, because of gravity fluid moves out of the legs and accumulates in the thorax. We hypothesized that fluid shifting out of the legs into the thorax contributes to the intrathoracic airway narrowing in asthma. Healthy and asthmatic subjects sat for 30 min and then lay supine for 30 min. To simulate overnight fluid shift, supine subjects were randomized to receive increased fluid shift out of the legs with lower bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…Since there is a strong inverse relationship between airway diameter and airway resistance (West, 2008 ), it may be expected that these differences in airway response to rostral fluid shifts between healthy and asthmatic subjects may be related to the differences in baseline airway caliber. Indeed, in our recent study (Bhatawadekar et al, 2017 ), as well as in other studies (Duggan et al, 2004 ; Cavalcanti et al, 2006 ), asthmatic subjects had greater respiratory resistance and stiffness than did healthy subjects at baseline in both upright and supine positions, thus implying differences in the baseline airway caliber. Therefore, it may be concluded that for similar amount of fluid accumulation in the lower airways walls, airways with a smaller lumen will have more narrowing and consequently more pronounced increase in their resistance compared to airways with a larger lumen.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Since there is a strong inverse relationship between airway diameter and airway resistance (West, 2008 ), it may be expected that these differences in airway response to rostral fluid shifts between healthy and asthmatic subjects may be related to the differences in baseline airway caliber. Indeed, in our recent study (Bhatawadekar et al, 2017 ), as well as in other studies (Duggan et al, 2004 ; Cavalcanti et al, 2006 ), asthmatic subjects had greater respiratory resistance and stiffness than did healthy subjects at baseline in both upright and supine positions, thus implying differences in the baseline airway caliber. Therefore, it may be concluded that for similar amount of fluid accumulation in the lower airways walls, airways with a smaller lumen will have more narrowing and consequently more pronounced increase in their resistance compared to airways with a larger lumen.…”
Section: Introductionsupporting
confidence: 65%
“…On changing to the supine position as during sleep, the fluid is reabsorbed rapidly from the interstitial space to the intravascular space of the legs (Thompson et al, 1928 ; Fawcett and Wynn, 1960 ), and redistributed to the upper body, including to the thorax and neck. We refer here to this process as a rostral fluid shift (Bhatawadekar et al, 2017 ). Evidence suggests that in asthma, nocturnal rostral fluid shift to the thorax during sleep may play a role in the pathogenesis of overnight airway narrowing in asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the included studies did not evaluate overnight changes in lung function, it is unlikely that exercise training will cause overnight changes if it did not change daytime lung function. Another factor that may be associated with the nocturnal worsening of asthma is the overnight rostral fluid shift from the legs to the thorax which can increase fluid accumulation in the lower airway wall, narrow airway lumen, and worsen asthma symptoms [ 25 , 26 ]. Previous studies in patients with sleep apnea have shown that physical training during the day can reduce overnight fluid shift out of the legs and improve sleep apnea severity [ 89 ] and snoring [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…During sleep, recumbent posture causes a reduction in the lung volumes, respiratory muscle tone, and lung compliance [ 22 24 ]. Moreover, recumbent posture also causes a shift of fluid from the legs to the thorax (rostral fluid shift) that is associated with airway narrowing in asthma [ 25 , 26 ]. In addition, during sleep there is an overnight decrease in plasma cortisol and an increase in airway inflammation, which in turn increases cholinergic tone [ 16 , 17 ], and enhances airway hyper-responsiveness.…”
Section: Introductionmentioning
confidence: 99%